A study on financial performances for selected commercial banks in Malaysia from 2004 to 2008 during financial crisis / Aminah Shari - Shari, Aminah (Faculty of Business and Management, 2009)
The purpose of this paper is to analyze the financial performance in the case of Commercial Banks in Malaysia during the period 2004-2008 during the financial crisis. The paper examines the impact of financial crisis to banks financial performance. My results show that leverage, liquidity and profitability significantly not affect banks financial performances. My results indicates that the during financial crisis the banking industry in Malaysia are not hit much to the banks performances, thus my study findings does not support the theoretical views according to the Bank Negara Malaysia Governor Tan Sri Dr Zeti Akhtar Aziz said that the financial market in Malaysia has been affected by the global financial crisis.